Literature Review: The Effect of Lutein Compounds on Cognitive Function in Adulthood - Maheswari, Nabila Amanda (JURNAL KESMAS DAN GIZI (JKG), 2025)
Cognitive function is related to the brain's ability to obtain, retain, and understand the information obtained. Decreased cognitive function can have an impact on a person's activities. Impaired cognitive function generally occurs with increasing age. Several studies show the effect of giving lutein as an antioxidant that can maintain brain health. Several studies have stated that there is a link between the body's plasma lutein levels and better cognitive function. This study was carried out with the aim of analyzing research results related to intervention of lutein and its isomers on cognitive function in adulthood. The literature analyzed is publications in the last 10 years with research designs in the form of RCTs and double blinds. Literature search using keywords (lutein or carotenoids) and (brain or cognition or cognitive function). Supplementation is considered to be able to help concentration in answering questions. However, supplementation is also considered to have no significant effect on cognitive function. Through analysis of all literature, it was found that lutein is able to maintain cognitive function in adults, especially memory. Further research is needed regarding lutein supplementation with other substance activators.